Performance Evaluation and Evaporation Loss Prediction in Counter Flowinduced Draft Geothermal Wet Cooling Tower Type Through Computational Fluid Dynamics (CFD) Simulation - Mukhamad Nashir; Moh. Djaeni; Muchammad Muchammad (Green Publisher Indonesia, 2026)
Cooling towers are critical components in geothermal power generation systems, playing a vital role in maintaining thermal efficiency and managing water resources. This study investigates the thermal performance and water loss due to evaporation in an induced draft counter-flow cooling tower using a modeling and simulation approach based on Computational Fluid Dynamics (CFD). Validation of the simulation results against actual data demonstrated high accuracy, with an error margin of 1.8%, indicating that CFD is a reliable method for analyzing and optimizing cooling tower design Simulation results show that increasing the hot water inlet temperature from 35°C to 49°C leads to a rise in evaporation loss from 5.0 kg/s to 13.0 kg/s (CFD), while the ASHRAE method yields higher values, ranging from 5.5 kg/s to 14.5 kg/s. For variations in hot water mass flow rate (423–845 kg/s), the ASHRAE method exhibits a linear increase in evaporation loss, whereas CFD results remain relatively stable. Additionally, increasing the hot water mass flow rate causes the cold-water outlet temperature to decrease from 21°C to 11°C, accompanied by a reduction in system effectiveness from 92% to 86%. Furthermore, increasing the cold air inlet velocity from 3.5 m/s to 6.5 m/s raises the evaporation loss from 14.5 kg/s to 16.0 kg/s (CFD) and significantly enhances system effectiveness from 11% to 91%. Overall, the findings demonstrate that CFD simulations provide realistic performance estimations compared to empirical methods, particularly under dynamic operating conditions.